2021
DOI: 10.1111/trf.16359
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of CD177‐reactive iso‐ and auto‐antibodies

Abstract: Background CD177 is a surface protein on neutrophils and a main mediator for the surface expression of proteinase 3 (PR3). Its functions are largely unknown. At least three types of antibodies have been described to target CD177: isoantibodies, which are formed in CD177‐null individuals as a result of an immune reaction following transfusion or pregnancy; autoantibodies present in sera from patients with autoimmune neutropenia; and antineutrophil cytoplasmic antibodies in sera from patients with glomerulonephr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Analysis has introduced an epitope formed by CD177/PR3 complex as a relevant epitope for CD177 autoantibodies but not isoantibodies. Interestingly this epitope is a signaling relevant epitope that upon binding of relevant antibodies induces neutrophil activation [63]. A previous study indicated CD177 as a heterophilic binding partner for platelet endothelial cell adhesion molecule 1 (PECAM-1).…”
Section: Nb Antigenmentioning
confidence: 99%
“…Analysis has introduced an epitope formed by CD177/PR3 complex as a relevant epitope for CD177 autoantibodies but not isoantibodies. Interestingly this epitope is a signaling relevant epitope that upon binding of relevant antibodies induces neutrophil activation [63]. A previous study indicated CD177 as a heterophilic binding partner for platelet endothelial cell adhesion molecule 1 (PECAM-1).…”
Section: Nb Antigenmentioning
confidence: 99%
“…For example, it is unknown if certain subpopulations of neutrophils are specific targets of immune mechanisms, for example, those expressing CD177 or those interacting with structures on endothelial cells significant for transmigration to the tissues or from the tissues back to PB or BM, and those interacting with organ-specific epitopes. 52 Likewise, it is unknown if there are recognition signals of neutrophil subpopulations for interaction with cytotoxic T-lymphocytes, NK cells, monocyte/macrophages, MDSC, and other cells that are involved in elimination or cross-talks with neutrophils. 15,17,39,45,53,54 Other possible mechanisms for AINP Cellular immune mechanism, implicating clonal or oligoclonal expansions of T-cell and NK-cell populations, may also account for NP particularly in adults.…”
Section: Redistribution As a Cause Of Blood Npmentioning
confidence: 99%
“…Accordingly, HNA‐2 null human subjects are prone to produce anti HNA‐2 isoantibodies. HNA‐2 isoantibodies are involved in a number of disorders such as neonatal alloimmune neutropenia, autoimmune neutropenia, drug‐induced immune neutropenia, and graft failure following marrow transplantation 6–10 . Additionally, HNA‐2 isoantibodies cause transfusion related acute lung injury (TRALI) and various pulmonary disorders 11–14 .…”
Section: Introductionmentioning
confidence: 99%
“…HNA-2 isoantibodies are involved in a number of disorders such as neonatal alloimmune neutropenia, autoimmune neutropenia, drug-induced immune neutropenia, and graft failure following marrow transplantation. [6][7][8][9][10] Additionally, HNA-2 isoantibodies cause transfusion related acute lung injury (TRALI) and various pulmonary disorders. [11][12][13][14] Consequently, HNA-2 is considered as one of the most important neutrophil antigens in human medicine.…”
Section: Introductionmentioning
confidence: 99%